Aspects influencing teacher’s motivation in private schools amid the challenging environment in Lebanon - Hanan Kontar; Nisrine Rizk; Nada Jabbour Al Maalouf (Quality Education for All)
Purpose – The purpose of this study is to pinpoint the factors that affect teacher motivation in this particular setting. It specifically looks at how job satisfaction, the reward system, training and development and work situational factors affect teachers’ motivation. Design/methodology/approach – Through nonrandom sampling, data from 229 teachers from private schools in Lebanon were gathered. Findings – The findings showed that professional training and development opportunities and a supportive work environment have a strong impact on teachers’ motivation. Originality/value – The findings highlight the need for more research to guide comprehensive improvement strategies in Lebanese private schools for motivating teachers. The Ministry of Education and private schools in Lebanon can benefit from the insights provided by the findings in terms of policy and practice. Among the suggestions include bringing up-to-date rules to boost teacher satisfaction, raising educational standards, creating focused training sessions, changing compensation systems and improving both the physical and mental aspects of the workplace.